„Why mothers die“: Was wir von der Analyse anästhesiebedingter mütterlicher Sterbefälle (1985–2013) gelernt haben = “Why mothers die” : Learning from the analysis of anaesthesia-related maternal deaths (1985–2013) - Neuhaus, Sophie; Neuhaus, Christopher; Fluhr, Herbert; Hofer, Stefan; Schreckenberger, Rosemarie; Weigand, Markus A. (Der Anaesthesist, 2016)
Every day, more than 800 women die from causes related to pregnancy or childbirth. Since 1952 the Confidential Enquiry of Maternal Deaths Reports (CEMD) have collected and analysed data on maternal mortality in the United Kingdom and Northern Ireland. This publication analyses the CEMD from 1985-2013 regarding anaesthesia- and analgesia related maternal deaths during pregnancy or peripartum. During this period, there has been a reduction in directly anaesthesia-related maternal deaths to 4.3 %. Yet, an increase in anaesthesia-associated maternal deaths has been recorded. The rate of fatal complications during obstetric regional anaesthesia doubled in recent years, while the fatality risk for obstetric general anaesthesia has decreased. Many of the reported maternal deaths could presumably have been avoided. The anaesthesiologist has to be familiar with state-of-the-art, guideline-based concepts for anaesthesia during pregnancy, childbirth or post partum, especially using tools like simulation. Vital sign monitoring after obstetric anaesthesia has to be identical to other postoperative monitoring, and Modified Early Warning Scores should be used for this purpose. In regional anaesthesia, current standards for hygiene have to be adhered to and patients have to be visited after spinal/epidural anaesthesia. Interdisciplinary communication and collaboration still have to be improved; careful interdisciplinary planning of childbirth in high-risk obstetric patients is strongly advised.
Gesehen am 21.11.2019